Application of a sensitive and accurate LC‐MS/MS method for determination of dryocrassin ABBA in rat plasma for a bioavailability study. (4th February 2014) - Ding, Ya‐Ming; Liu, Zhuo; Li, Fu‐Qiang
ABSTRACT A sensitive and accurate liquid chromatography–tandem mass spectrometry method was developed and validated for the determination of dryocrassin ABBA, a potential active component isolated from Dryopteris crassirhizoma, in rat plasma. Chromatographic separation was achieved on a Zorbax SB‐C18 column (50 × 2.1 mm, 1.8 µm), with elution consisting of eluent (A) 10 mm ammonium acetate in methanol containing 0.1% formic acid and (B) 10 mm ammonium acetate in water containing 0.1% formic acid (A:B = 99:1, v/v) at a flow rate of 0.3 mL/min. Multiple reaction monitoring mode was used to monitor the precursor–product ion transitions of m/z 819.3 → 403.4 for dryocrassin ABBA and m/z 426.2 → 409.2 for internal standard. This assay exhibited a good linearity with a correlation coefficient >0.99 and showed no endogenous interference with the analyte and internal standard. The lower limit of quantification of dryocrassin ABBA was 4 ng/mL in 50 μL of rat plasma. The method was successfully applied in the pharmacokinetic study of dryocrassin ABBA in rats after intravenous (2.35 mg/kg) and oral (23.5 mg/kg) doses of dryocrassin ABBA. The oral bioavailability (F) of dryocrassin ABBA was estimated to be 50.1%. Our study is the first to clarify the pharmacokinetic behaviors of dryocrassin ABBA in animals. Copyright © 2014 John Wiley & Sons, Ltd.